Members of the XIth Brigade as guests of the Spanish children's home "Ernst Thälmann", with its director Louis Habermann. Place of persons on back. Copied from collection Museum für Deutsche Geschichte
Members of the XIth Brigade as guests of the Spanish children's home "Ernst Thälmann", with its director Louis Habermann. Place of persons on back. Copied from collection Museum für Deutsche Geschichte.